2006
DOI: 10.1115/1.2241839
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Heat Conduction Across Metal-Dielectric Interfaces

Abstract: We report a theoretical study of heat conduction across metal-dielectric interfaces in devices and structures of practical interest. At cryogenic temperatures, the thermal interface resistance between electrodes and a substrate is responsible for substantial reduction in the maximum permissible peak power in Josephson junctions. The thermal interface resistance is much smaller at elevated temperatures but it still plays a critical role in nanoscale devices and structures, especially nanolaminates that consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The third effect is describable with a continuum two-fluid model. 11,12 These three causes reasonably coexist; inelastic scattering between electrons in metal and phonons in dielectric is rarely considered in previous literatures due to its insignificant effect, as for the thermal resistances caused by phonon-phonon scattering at the interface and by electron-phonon nonequilibrium near the interface in metal, Majumdar and Reddy 12 suggested that they are in series. In this work, we used a sandwiched film structure, which an ultrathin pure metal layer is sandwiched between two dielectric layers, to calculate the theoretical value by using a continuum two-fluid model and also to measure the metal-dielectric interfacial thermal resistance.…”
mentioning
confidence: 96%
“…The third effect is describable with a continuum two-fluid model. 11,12 These three causes reasonably coexist; inelastic scattering between electrons in metal and phonons in dielectric is rarely considered in previous literatures due to its insignificant effect, as for the thermal resistances caused by phonon-phonon scattering at the interface and by electron-phonon nonequilibrium near the interface in metal, Majumdar and Reddy 12 suggested that they are in series. In this work, we used a sandwiched film structure, which an ultrathin pure metal layer is sandwiched between two dielectric layers, to calculate the theoretical value by using a continuum two-fluid model and also to measure the metal-dielectric interfacial thermal resistance.…”
mentioning
confidence: 96%
“…When considering the pathway (2), one usually applies the phenomenological two-temperature model [13] that has been widely used to investigate the ultrafast pulsed laser heating of metals [14,15], and assume the pathway (3) is negligible [8,9]. However, when the imperfect interface or the large lattice-mismatch of metal and dielectric is present, both pathway (1) and (2) will be seriously suppressed and the pathway (3) becomes significant.…”
mentioning
confidence: 99%
“…Hence, for metal-dielectric interfacial heat transport, energy transfer includes three possible pathways: (1) energy exchange between phonons in metal and phonons in dielectric, which is widely studied with the acoustic and diffuse mismatch models [3][4][5][6]; (2) nonequilibrium electron-phonon (e-ph) energy exchange within the metal, with subsequently phonon-phonon coupling across the interface [7][8][9]; (3) direct energy transfer from electrons in metal to phonons in dielectric through inelastic scattering induced by e-ph coupling across the interface [10][11][12].…”
mentioning
confidence: 99%
“…It has been suggested that there is an effective boundary resistance due to nonequilibrium between different temperature baths in a region near the film/substrate interface [60,39]. The non-equilibrium region is a result of different boundary conditions for the different baths.…”
Section: Heat Transfer Into the Substratementioning
confidence: 99%